Norms for standard neuropsychological tests from the French CONSTANCES cohort. (20th January 2019) - Ouvrard, C.; Berr, C.; Meillon, C.; Ribet, C.; Goldberg, M.; Zins, M.; Amieva, H.
Abstract : Background and purpose: Neuropsychological testing plays a key role in various clinical contexts. Even though a substantial number of adults suffer neurological disorders such as early‐onset dementia, stroke, traumatic brain injury or multiple sclerosis, most normative data do not include persons below 65. The aim of this study was to produce updated norms for the Mini‐Mental State Examination, the Free and Cued Selective Reminding Test, the Trail Making Test, verbal fluency tasks and the Digit Symbol Substitution Test for middle‐aged and older adults. Methods: The sample consisted of 51 879 participants aged 45–70 years from the CONSTANCES study. Norms are presented in percentiles stratified on age, education and gender. Results: The results illustrated the effect of age in all tests considered. For tests involving speed processing, the impact of age was observed including in tight age range categories (5 years). The results also showed the well‐known effect of education and an effect of gender in tests involving verbal memory and speed processing. Conclusions: The norms provided allow the variability of the cognitive performances of middle‐aged to older populations to be understood, with a high precision in age categories. The tests considered are broadly used in neuropsychological practice and should be helpful in a variety of clinical contexts.